Epistemologi Kurikulum Pendidikan Sains - Humaidi, Humaidi (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2013)
Curriculum is used as well as the way, plans, rules, teaching materials, and guidelines in the learning process. It is also meaningful as a map of reality. Curriculum is similar as a road map and a map of the world that becomes a guidance and direction for people who are traveling. Curriculum is a map of reality because it becomes a clue, for example, any form of reality and physical, metaphysical, mathematical, social-that can be reviewed and learnt by humans. As a map, it serves as a guideline to observe, to read, and to review some forms. In addition, the curriculum can be functioned and used as a tool by people to actualize their potency, so they can be professional in education.